Exploration Students’ Experiences of Integrating Japanese Popular Culture Based Digital Content in Japanese Language Learning: Communicative Competence and Intercultural Awareness - Muhammad Thamrin; Robihim; Kun Makhsusy Permatasari (Raja Zulkarnain Education Foundation, 2026)
This study was conducted in response to the growing use of digital media and Japanese popular culture in Japanese language learning in the era of technological openness and globalization. The study aims to explore students’ experiences of integrating Japanese popular culture–based digital content in learning Japanese and to examine its contribution to communicative competence and intercultural awareness. Using a qualitative case study design, the study involved 40 third- and fifth-semester students. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed thematically. The findings show that the use of Japanese popular culture–based digital content supports students’ understanding of vocabulary, sentence structures, and appropriate expressions, increases speaking confidence, and enhances awareness of Japanese cultural values and communication norms. However, students’ interactive speaking skills and two-way communication ability remain limited, and difficulties in interpreting implicit meanings and applying politeness strategies persist. In conclusion, Japanese popular culture–based digital content is beneficial for developing linguistic awareness and intercultural understanding, but its effective impact on communicative competence requires pedagogical mediation, interaction-based tasks, and guided cultural reflection